INFLUENCE OF FAMILY ENVIRONMENT ON PROSOCIAL ATTITUDE OF STUDENT TEACHERS AT SECONDARY LEVEL - Rose Mary J. S, Dr. K. B. Jasmine Suthanthira Devi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The present era is a period of knowledge explosion and high-tech life. But it does not mean that the quality of life has been improved. Selfishness and individualism pervades all walks of life. In this scenario it is imperative for secondary school teachers to demonstrate prosocial tendencies as they have to deal with students of adolescent period and in turn to lead the society through the desirable path and direction. The present study attempts to explore the relationship between family environment and prosocial attitude of student teachers through a normative survey. Two hundred student teachers were assessed for their family environment and prosocial attitude respectively by using a family environment scale (Bhatia & Chadha, 2004) and a prosocial attitude scale prepared by the investigator. The inferential statistical analysis shows that there exists significant, positive, and substantial relationship between family environment and prosocial attitude of student teachers. The study reveals the worth of family environment in developing prosocial attitude and tendencies among student teachers.